IMPLEMENTING BLENDED LEARNING METHOD AT MTSN 2 PROBOLINGGO - Laila Misbahatul Mukarromah (Educational Research Indonesia, 2024)
This research aims to describe the implementation of blended learning method at MTSN 2 Probolinggo through a case study with descriptive qualitative approach. Data was collected through virtual in-depth interviews with students and teachers, as well as analysis of assessment documents and learning tools such as lesson plans. The results show that Blended Learning is effective in improving students' understanding of the subject matter and increasing students' engagement in the learning process. The majority of students feel the benefits of this method, especially in terms of material accessibility and deeper understanding through face-to-face sessions. However, challenges such as unstable internet connectivity and technology training needs for teachers still need to be addressed. Periodic evaluation and constructive feedback from teachers are also important to optimize the implementation of blended learning. With support from various parties, including the school and government, Blended Learning can be a relevant and effective learning method at MTSN 2 Probolinggo, preparing students to face future challenges and achieve the desired educational goals